Respuesta :
Answer:
Avery is right, because [tex]g(x) = f(x)+2[/tex].
Cindy is right, because [tex]g(x) = f(x+1)[/tex].
Step-by-step explanation:
Let [tex]f(x)[/tex] and [tex]g(x)[/tex] functions, then [tex]g(x)[/tex] is the vertical translated version of [tex]f(x)[/tex] if and only if:
[tex]g(x) = f(x)+k[/tex], [tex]\forall \,k\in \mathbb{R}[/tex]
[tex]k = g(x)-f(x)[/tex]
If we know that [tex]f(x) = 2\cdot x + 1[/tex] and [tex]g(x) = 2\cdot x + 3[/tex], then:
[tex]k = (2\cdot x + 3) - (2\cdot x +1)[/tex]
[tex]k = 2[/tex]
Then, Avery is right, because [tex]g(x) = f(x)+2[/tex].
Let [tex]f(x)[/tex] and [tex]g(x)[/tex] functions, then [tex]g(x)[/tex] is the horizontal translated version of [tex]f(x)[/tex] if and only if:
[tex]g(x) = f(x+k)[/tex], [tex]\forall \,k\in \mathbb{R}[/tex]
If we know that [tex]f(x) = 2\cdot x + 1[/tex] and [tex]g(x) = 2\cdot x + 3[/tex], then:
[tex]g(x) = 2\cdot x + 3[/tex]
[tex]g(x) = 2\cdot x + 2 + 1[/tex]
[tex]g(x) = 2\cdot (x+1)+1[/tex]
[tex]g(x) = f(x+1)[/tex]
Then, Cindy is right, because [tex]g(x) = f(x+1)[/tex].